1990
DOI: 10.1111/j.1365-2125.1990.tb03679.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and bioavailability of omeprazole after single and repeated oral administration in healthy subjects.

Abstract: 1. Ten healthy subjects were given 20 mg omeprazole EC (enteric coated) granules once daily for 8 days. An i.v. tracer dose of [14C]‐omeprazole was given simultaneously with the first and last oral doses and blood sampling was performed thereafter. In order to study the extent of absorption at minimal acid exposure, a single dose of 20 mg omeprazole was also given as a buffered solution, before and after the treatment with EC granules. 2. Kinetic parameters of omeprazole after the i.v. tracer dose were unchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 10 publications
(12 reference statements)
7
70
0
1
Order By: Relevance
“…The kinetic parameters after multiple omeprazole doses resemble those reported by other authors. 7,12,13 However, a direct comparison is difficult because omeprazole kinetics vary with dose, duration of treatment, and with CYP2C19 phenotype. The threefold increase of AUC following a dose escalation of only 50% from 40 to 60 mg seems to be more pronounced than in studies using lower omeprazole doses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The kinetic parameters after multiple omeprazole doses resemble those reported by other authors. 7,12,13 However, a direct comparison is difficult because omeprazole kinetics vary with dose, duration of treatment, and with CYP2C19 phenotype. The threefold increase of AUC following a dose escalation of only 50% from 40 to 60 mg seems to be more pronounced than in studies using lower omeprazole doses.…”
Section: Resultsmentioning
confidence: 99%
“…The threefold increase of AUC following a dose escalation of only 50% from 40 to 60 mg seems to be more pronounced than in studies using lower omeprazole doses. [7][8][9][10][11][12][13] With respect to metabolite kinetics, a good correlation between elimination parameters of omeprazole and omeprazole sulfone was reported after single doses, 9 This finding could be reproduced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies with repeated once daily oral administration of omeprazole as EC granules in different doses have shown that the AUC increases during the first 4 days of treatment with no further rise thereafter during continued treatment (Andersson et al, 1990;Muller et al, 1983;Prichard et al, 1985). The increase in AUC has also been shown to be dose-dependent between 10 and 40 mg with a more pronounced increase with higher doses (Andersson et al, 1989).…”
Section: Introductionmentioning
confidence: 71%
“…Considerable interindividual variability, particularly in area under the plasma concentration-time curve (AUC) data, has been described before for both intravenous and oral administration of omeprazole in children [6,7] and adults [8,9]. This high variability can be largely attributed to genetic polymorphism of the cytochrome P450 (CYP) isoform CYP2C19 [4,10].…”
Section: Discussionmentioning
confidence: 99%